Higiene sanitasi makanan dan analisis nomor P-IRT pada kerupuk berwarna merah (Studi pasar Kepanjen Kabupaten Malang) - Dieka armanda kurniasari; Rahayu Sri Pujiati; Prehatin Trirahayu Ningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Food sanitation hygiene has been done to control food factor, people, place and tools in order to prevent cross contamination between food and eater. Household food industry must possess household food industry certificate or SPP-IRT to aid supervision by involved parties. The aim of this research was to discover food sanitation hygiene and analysis P-IRT number on red-coloring crackers at Kepanjen Market in Malang. Thisresearch is descriptive research with observation and interview methods to cracker industry workers and there were 12 kinds of red-coloring crackers distributed around Kepanjen Market. The research used univariant analysis to describe variable of those which were observed. This research it was found that there were three stages in cracker making process, Food sanitation hygiene, and P-IRT number on red-coloring crackers. From this research there were 3 of respondents around < 40 years old, all respondents in secondary education, and 2respondents had < 3 years of working period. The application of food hygiene and sanitation of cracker industry in Malang Regency was categorized as relatively good. There were 7 red-coloring crackers traded at Kepanjen Market were qualified as what had been standardized by BPOM number 22 year 2020. Meanwhile, there were 4 products were not updated and 1 product was not qualified.